A new hand enhances life for quadruple amputee: A single case study. (September 2014) - Anjou, Katie; Gibbs, Josephine; Purtell, Daniel; Morrison, Wayne
This single case study discusses the various challenges and rehabilitation of Australia's first hand transplant from the hand therapy perspective. The recipient was a 65-year-old quadrimembral amputee male following overwhelming pneumococcal sepsis. Key issues included cognitive relearning following the four-year loss of cortical feedback, extrinsic muscle retraining, poor coordination and functional limitations as a result of intrinsic dennervation, and an insensate hand. Distinct clinical differences from total hand replantation included consideration of immunosuppression drugs and potential rejection episodes. Although the patient was highly motivated, a client-centred approach was critical for ongoing commitment to the intensive long-term rehabilitation programme. The recipient's progress in the first two and a half years has been impressive with achievement of many personal goals including eating, drinking, writing, driving and lawn bowls. His results, recorded on the International Hand Transplant Registry, showed superior measurements in areas of the DASH, grip strength, and TAM of forearm, wrist, and fingers.